Holy Bible [compact disc, unabridged] : Prophets of the Old Testament, Part 4. (Recorded Books, LLC, 2004)
Word-for-word unabridged recording of Hosea, Joel, Amos, Obadiah, Jonah, Micah, Nahum, Habakkuk, Zephaniah, Haggai, Zechariah, and Malachi, narrated in contemporary language for easy understanding.